Flame Propagation and Combustion State Transition in a Sub-millimeter Constant-volume Space. Issue 11 (18th August 2021) - Su, Hang; Huo, Jiepeng; Wang, Xiaohan; Jiang, Liqiao; Song, Qianshi; Zhao, Daiqing
ABSTRACT: Experimental studies on premixed flame propagation characteristics in a sub-millimeter-scale closed chamber are performed. Propane/air mixtures are ignited in the center of the visualized chamber and the subsequent flame front evolution process is recorded. The effects of the gap size of the chamber and the initial pressure of the mixture on the flame behaviors are investigated. In the condition of the gap size H = 0.45 mm, the flammable range of propane/air mixtures ranges from 2.0 bar to 3.0 bar of initial pressure P 0, and from 0.9 to 1.5 of the equivalence ratio φ . At H = 0.45 mm, the flammability limit of the mixture is lower than that of large scale, and the instability of flame propagation is higher. With suitable initial conditions, such as P 0  ≥ 2.5 bar, φ  = 1.2 ~ 1.3, and H = 0.45 mm, the transition from a low-speed laminar flame to a high-speed deflagration flame is observed. When the size of the combustion chamber height is as small as the laminar flame surface thickness, acoustic waves in the combustion chamber dominate flame propagation. The interaction between the acoustic wave and the flame front greatly increases the flame surface area, resulting in great enhancement of reaction and subsequent flame deflagration. Furthermore, the increase in initial pressure will dramatically increase the propagation speed and the pressure peak, which are also affected notably by the equivalence ratio and the spatial scale of the chamber.